Gas-Phase Synthesis of Film Structures of Ni—N System - Shalaev, R.V. (Металлофизика и новейшие технологии, 2015)
As shown, the magnetron sputtering is effective for the synthesis of various nanostructured phases of nickel nitride (solid solution of nitrogen in nickel, Ni₄N, Ni₃N, and Ni₂N). The regularities of formation of globular or nanocolumnar film structures are determined, depending on the concentration of nitrogen in the buffer gas.